Co-doping strategies for advanced solid state electrolytes with lithium salt: A study on the structural and electrochemical properties of LATP - Hassaan, Shahid; Khadija, Nasir; Ahmad, Haseeb; Ali, Ghulam; Shahid, Bashir; Quazi, M. M. (IOP Publishing Ltd, 2024)
The commercialization of lithium-ion batteries has revolutionized the field of energy storage, yet their usage of organic electrolytes has led to significant safety concerns. Solid-state electrolytes have emerged as a promising solution to these issues, enabling the development of high-performance solid-state lithium batteries. The NASICON-type solid electrolyte Li1.3Al0.3Ti1.7P3O12 (LATP) has demonstrated excellent properties and significant potential. This study involves the solid-state synthesis of LATP electrolytes doped with Cobalt and Silicon. Furthermore, adding 8% LiBr into LATP-0.04 significantly enhanced ionic conductivity, reaching a value of 3.50 × 10−4 S cm−1. This can be linked to lithium salt filling vacant spaces between grains, resulting in a significant drop in grain boundary resistances. The electrochemical analysis through Linear Sweep Voltammetry (LSV) indicates that the investigated material demonstrates the capability to sustain stability and functionality even under the influence of elevated voltages, notably up to 5.45 V. These findings imply that optimal cobalt doping and Lithium salt contribute to superior ionic conductivity compared to pristine LATP.